The brittle-ductile transition of tungsten single crystals at the micro-scale. (15th August 2018) - Ast, J.; Schwiedrzik, J.J.; Wehrs, J.; Frey, D.; Polyakov, M.N.; Michler, J.; Maeder, X.
Abstract: The loading rate effect on the brittle-ductile transition temperatures of tungsten single crystals at the micro-scale was investigated by microcantilevers with a (100)[001] crack system. Specimens with a length to width to height of 15 μm/4 μm/6 μm were fabricated by focused ion beam milling. At low temperatures (−90 to −25 °C) the samples failed by brittle cleavage fracture, irrespective of the applied loading rate at a fracture toughness of 3.2 MPa·m 1/2 . With increasing temperatures up to 500 °C and depending on the applied loading rate, the fracture toughness increased and significant crack tip plasticity and dislocation-controlled microcleavage were observed by means of high resolution electron backscatter diffraction measurements performed after testing. With respect to macroscopic specimens, a shift of the brittle-ductile transition to lower temperatures and a significantly lower activation energy of the brittle-ductile transition of 0.36 eV were found. We explain this by the increase in flow stresses due to sample size effects. Graphical abstract: Unlabelled Image Highlights: Determination of fracture toughness at the micro-scale as a function of loading rate, temperature and specimen size Measurement of J-Δa curves from in-situ micro-cantilever tests performed in the temperature range between -90 °C and 500 °C Discussion of activation energy for the brittle-ductile transition with respect to specimen size effects Analysis of crack tip plasticity by high-resolution electron backscatter diffraction and transmission electron microscopy